The Risk of Hospitalizations with Injury Diagnoses in a Matched Cohort of Children and Adolescents with and without Attention Deficit/Hyperactivity Disorder in Germany: A Database Study - Lindemann, Christina; Langner, Ingo; Banaschewski, Tobias; Garbe, Edeltraut; Mikolajczyk, Rafael T. (Frontiers in Pediatrics, 2017)
Background: Attention deficit / hyperactivity disorder (ADHD) is a common neuropsychiatric disorder in children and adolescents worldwide, and children with ADHD have elevated risk of injuries. Our aim was to assess the risk of hospitalizations with injury diagnoses and their various subtypes in children and adolescents with newly diagnosed ADHD compared to those without ADHD, as well as to study sex effects on this risk in the setting of the German health care system. Methods: The German Pharmacoepidemiological Research Database (GePaRD), in which 20 million insured from four statutory health insurances in Germany are included, was used to set up a matched cohort study of 3 to 17-year-old children and adolescents with and without ADHD. We calculated age-specific incidence rates and used Cox regression to obtain hazard ratios (HR) for hospitalizations with injury diagnoses. We used the injury mortality diagnosis matrix for classification of injuries. Results: The matched cohort comprised a total of 75,300 children. The age-specific incidence rates for hospitalization with injury diagnosis for males with ADHD displayed a u-shaped form with highest incidences in the in the age groups 3-6 years (26.2 per 1000 person-years; 95% confidence interval 20.5-33.0) and 18-21 years (28.6; 22.4–36.0). Girls with ADHD were less affected in younger age-groups, but the incidence rate for 18-21 year olds was similar to boys with ADHD (26.4; 17.4-38.4). The adjusted HR for children with ADHD was 1.40 (95% CI 1.30–1.49) compared to non-affected children. With respect to nature of injury, ADHD was associated with hospitalization with injury diagnoses of the internal organs, open wounds, and contusions but not with other injuries. With respect to body regions, children with ADHD were more prone to hospitalizations with injuries of the abdomen, traumatic brain injuries, other head injuries, and system-wide injuries such as poisoning and intoxication. No significant associations were seen for the other body regions. Differences between sexes were only seen for system-wide injuries. Conclusion: Children and adolescents with ADHD are at an increased risk for hospitalizations with diagnoses of injuries compared to non-affected children. Despite differences in health care systems, the risk increase is at a similar level